2015
DOI: 10.1073/pnas.1502370112
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of end-joining repair for efficient site-specific gene insertion after TALEN/CRISPR mutagenesis inAedes aegypti

Abstract: Conventional control strategies for mosquito-borne pathogens such as malaria and dengue are now being complemented by the development of transgenic mosquito strains reprogrammed to generate beneficial phenotypes such as conditional sterility or pathogen resistance. The widespread success of site-specific nucleases such as transcription activator-like effector nucleases (TALENs) and clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 in model organisms also suggests that reprogrammable gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(135 citation statements)
references
References 53 publications
(61 reference statements)
2
133
0
Order By: Relevance
“…stephensi (15) was injected with a solution containing 100 ng/μL each of the pAsMCRkh2 plasmid, Cas9 protein, Cas9 doublestranded RNAs (dsRNAs), and Ku70 dsRNA. The rationale for including the dsRNAs was to silence expression of the incoming Cas9 gene (dsCas9) carried on the plasmid and to reduce activity of the nonhomologous end-joining (NHEJ) pathway (dsKU70) (31) to favor HDR-mediated insertion of the pAsMCRkh2 cargo. Genomic integration of the transgene was achieved by the coinjected Cas9 protein together with the kh2 gRNA encoded on the (28) and square (29).…”
Section: Resultsmentioning
confidence: 99%
“…stephensi (15) was injected with a solution containing 100 ng/μL each of the pAsMCRkh2 plasmid, Cas9 protein, Cas9 doublestranded RNAs (dsRNAs), and Ku70 dsRNA. The rationale for including the dsRNAs was to silence expression of the incoming Cas9 gene (dsCas9) carried on the plasmid and to reduce activity of the nonhomologous end-joining (NHEJ) pathway (dsKU70) (31) to favor HDR-mediated insertion of the pAsMCRkh2 cargo. Genomic integration of the transgene was achieved by the coinjected Cas9 protein together with the kh2 gRNA encoded on the (28) and square (29).…”
Section: Resultsmentioning
confidence: 99%
“…However, the recent application of Gal4-UAS systems with the miR-SP transgenic method has begun to shed new light on understanding miRNA function in non-drosophilid insects [19, 41]. Additionally, investigations of the CRISPR-Cas9 system offers promising results that will allow genome engineering previously not feasible for non-model organisms [5862]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, Mashiko demonstrated that microinjection of a plasmid encoding Cas9 and sgRNA into the pronucleus of mouse zygotes is a simple and convenient method to obtain a knockout mouse model within a month 52,53 . Similarly, microinjection of CRISPR-Cas9 was used to edit genes in the cells of rabbits 54 , zebrafish 55 , Ciona intestinalis 56 , worms 57 and Aedes aegypti 58 .…”
Section: Physical and Non-viral Delivery Of Crispr-cas9mentioning
confidence: 99%